Discovering linked data collections through a new national metadata platform - Miller, Kate M; Flack, Felicity; Smith, Merran; Marshall, Carina Ecremen; Bennett, Vicki (International Journal of Population Data Science, 2025)
Background Metadata plays a crucial role in the health research infrastructure ecosystem. Despite the abundance of metadata for data collections in Australia, the vast and diverse data custodian landscape poses challenges for linked data researchers to find relevant information for multiple data collections, often making it an arduous and time-intensive task. Methods The project comprised three phases: an initial scoping exercise to understand the current state of metadata and related best practice; a national consultation involving researchers, data linkage staff and data custodians to develop a high-fidelity prototype of a metadata platform; and a final build and implementation phase. The platform underwent several prototyping and testing cycles to refine the digital experience. Results Expert interviews confirmed that there is a wealth of metadata available, but it is difficult for researchers to access and evaluate. Consultations with researchers identified opportunities to standardise metadata across collections and provide a centralised platform to enhance the discoverability of data collections for research using linked data. High value platform features included searching, browsing and filtering capabilities, data item list metadata, standardised formats, sample data, and frequently asked questions. The final design and functionality reflected user consultations and data custodian input on feasibility. Conclusion The Population Health Research Network developed a metadata platform to enable researchers to evaluate the suitability of Australian data collections for linked data projects more effectively. The platform has standardised the way in which metadata is presented for data collections nationally. Improved metadata quality, readability and accessibility will save time and enhance the quality of applications for linked data.